Detasseling practices on tropical maize and its effect on mineral nutrition and nutricional efficiency - Vasconcellos, Carlos Alberto; Magalhães, Paulo Cesar; Durães, Frederico Ozanan Machado; Fernandes, Fernando Tavares (Pesquisa Agropecuaria Brasileira, 1995)
The effect of different methods of maize sterilization on two inbred lines (A and B) and their hybrid ( HS CMS 355) were studied in a Red Dystrophic Latosol from Sete Lagoas, Minas Gerais, Brazil, for grain production and nutritional efficiency. The tassel removal was accomplished by : manual cutting off, mechanical, manual cutting with 4-5 leaves involving the tassel, no cutting and male sterility. The different methods used for detasseling did not affect maize production, total dry matter or nutrient conversion into grains of the cultivars studied. However, the residual nutrients increased in the stalk with leaf sheaths, husks and cob when the tassel was removed. The percentage of nutrients conversion into grains does not mean necessarily maize varieties with more grain production by nutrient absorved.